1995
DOI: 10.1006/viro.1995.0024
|View full text |Cite
|
Sign up to set email alerts
|

Expression, Purification, and Identification of a Novel Self-Cleavage Site of the NIa C-Terminal 27-kDa Protease of Turnip Mosaic Potyvirus C5

Abstract: The gene encoding the C-terminal protease domain (27 kDa) of the nuclear inclusion protein a of turnip mosaic potyvirus C5 was cloned and expressed as a fusion protein with glutathione S-transferase in Escherichia coli XL1-blue. Two forms of the protease (27 and 25 kDa) were purified from the fusion protein by glutathione affinity chromatography and Mono S chromatography and exhibited the specific proteolytic activity when a synthetic undecapeptide, Glu-Pro-Thr-Val-Tyr-His-Gln-Thr-Leu-Asn-Glu, or an in vitro t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…In earlier studies, the activity of the recombinant NIa protease was assayed using a peptide containing the cleavage site and by the use of polyprotein substrates obtained by in vitro translation [5,17,18,22]. Hence, a nonapeptide (Ac-GGEVAHQAG-NH 2 ) corresponding to the cleavage site between the PVBV NIb and CP was synthesized, and was used as a substrate for the NIa protease.…”
Section: Expression Of Nib-cp In E Coli and Nia Protease Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…In earlier studies, the activity of the recombinant NIa protease was assayed using a peptide containing the cleavage site and by the use of polyprotein substrates obtained by in vitro translation [5,17,18,22]. Hence, a nonapeptide (Ac-GGEVAHQAG-NH 2 ) corresponding to the cleavage site between the PVBV NIb and CP was synthesized, and was used as a substrate for the NIa protease.…”
Section: Expression Of Nib-cp In E Coli and Nia Protease Assaymentioning
confidence: 99%
“…The NIa proteases from Tobacco etch potyvirus (TEV) and Turnip mosaic potyvirus (TuMV) have been overexpressed and purified [17,22] and the recombinant proteases were shown to be catalytically active. However, a truncated NIa protease lacking the C-terminal 20-24 amino acids, resulting from autocatalytic activity of the recombinant protease, was less active [17,18,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Processing of the potyviral polyprotein seems to be a finely regulated process that produces the right amounts of the different gene products in time and space (Merits et al, 2002). Regulation is mainly based on the specific amino acid sequence recognized by the viral NIaPro, with some processing sites being cleaved faster than others Parks et al, 1995;Kim et al, 1995). Insertion of NIb in some of the intercistronic positions of the polyprotein may have fatal effects on this regulation.…”
Section: Research Articlementioning
confidence: 99%
“…Despite of their apparent simplicity of this genome expression strategy, the processing of potyviral polyprotein seems to be finely regulated resulting in the production of viral proteins in the right amount, time and space (Merits et al, 2002;Ivanov et al, 2014). The regulation is mainly based on the recognition efficiency of a viral encoded protease, NIaPro, responsible for the proteolytic processing of the main genome block of potyviruses from P3 to the end of the polyprotein Parks et al, 1995;Kim et al, 1995). Several studies demonstrated that there are some intercistronic positions that enable insertion of foreign genes without interrupting viral functions resulting in viable chimeric viruses.…”
Section: >Zymv-crtb (Insert Between Possitions 8541-8542 Of Zymv-wt)mentioning
confidence: 99%